Early serum TARC reduction predicts prognosis in advanced‐stage Hodgkin lymphoma patients treated with a PET‐adapted strategy. Issue 4 (30th July 2020) - Viviani, Simonetta; Mazzocchi, Arabella; Pavoni, Chiara; Taverna, Francesca; Rossi, Andrea; Patti, Caterina; Romano, Alessandra; Trentin, Livio; Sorasio, Roberto; Guidetti, Anna; Gottardi, Daniela; Tarella, Corrado; et al.
Abstract: Among patients with advanced‐stage classical Hodgkin lymphoma (cHL) receiving ABVD chemotherapy, PET performed after the first two treatment cycles (PET‐2) has prognostic value. However, 15% of patients with a negative PET‐2 will experience treatment failure. Here we prospectively evaluated serum thymus and activation‐regulated chemokine (TARC) levels, to improve risk assessment in patients treated according to HD0607 PET‐driven trial (#NCT00795613). In 266 patients with available serum samples, who have agreed to participate in a sub‐study for assessment of the role of TARC monitoring, serum TARC levels were measured at baseline and at time of PET‐2 by commercially available ELISA test kits. The primary end‐point was to evaluate the association between TARC after 2 ABVD cycles and PFS. Median TARC‐2 values were significantly higher in PET‐2‐positive patients compared to PET‐2‐negative patients ( P = .001), and in patients with treatment failure compared to those in continuous CR ( P = .01). The 4‐year PFS significantly differed between patients with TARC‐2 >800 pg/mL vs ≤800 pg/mL (64% vs 86%, P = .0001). Moreover, among PET‐2‐negative patients, elevated TARC‐2 identified those with a worse prognosis (74% vs 89%; P = .01). In multivariable analysis, TARC‐2 >800 pg/mL was a significant independent predictor of PFS in the whole study population (HR 2.39, P = .004) and among the PET‐2‐negative patients (HR 2.49, P = .02). In conclusion, our results indicate that TARC‐2 serum levels above 800 pg/mL suggest the need for a stringent follow‐up in PET‐2‐negative patients, and the evaluation of new drugs in PET‐2‐positive, who will likely fail to respond to intensification with escalated BEACOPP.